2019
DOI: 10.1021/acs.joc.8b02792
|View full text |Cite
|
Sign up to set email alerts
|

Diarylborinic Acid-Catalyzed, Site-Selective Sulfation of Carbohydrate Derivatives

Abstract: Sulfated carbohydrates have been implicated in diverse biological processes, with the position and extent of sulfation of a glycoside often playing important roles in determining the affinity and specificity of its binding to a biomolecular partner. Methods for the site-selective introduction of sulfate groups to carbohydrates are thus of interest. Here, we describe the development of a diarylborinic acid-catalyzed protocol for selective sulfation of pyranoside derivatives at the equatorial position of a cis-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…15,16 The addition of catalytic diaryl borinic acid can be used with Me 3 NSO 3 to sulfate carbohydrates. 17 The limitations with these routes include the need for a stoichiometric excess of the reagent per alcohol group (up to 10 eq. per hydroxyl group) and difficulties with purification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The addition of catalytic diaryl borinic acid can be used with Me 3 NSO 3 to sulfate carbohydrates. 17 The limitations with these routes include the need for a stoichiometric excess of the reagent per alcohol group (up to 10 eq. per hydroxyl group) and difficulties with purification.…”
mentioning
confidence: 99%
“…We observed that 1 can achieve high conversions of 2a to 3a/4a without microwave irradiation (entries 1-7 vs. 14 and 15) unlike other reported sulfating agents. The addition of a hetero or homogenous base (entries [16][17][18][19] was investigated and in all cases this led to a decrease in conversion to 3a. Most notably, the addition of tributylamine (entry 19) initially increased the rate conversion to 3a, but reduced the overall conversion contradicting the original report.…”
mentioning
confidence: 99%
“…Over the past few decades, beginning with catalytic use of tin reagents, a wide variety of transition-metal catalysts, organocatalysts, and peptide catalysts have been developed. More recently, organoboron catalysis has emerged as a new approach for the site-selective activation of hydroxy groups. Organoboron compounds have been widely used as regioselective protective or transient masking agents for carbohydrates and polyols by taking advantage of their high molecular recognition ability for cis -vicinal or 4,6-diols moieties of unprotected hexapyranosides, affording five- or six-membered cyclic boronic esters (Figure a) . Tricoordinated cyclic organoboronic esters attenuate the nucleophilicity of boron-bound oxygen atoms by the flow of lone-pair electrons of oxygens to the empty p-orbital of boron atom.…”
mentioning
confidence: 99%
“…[12,13] However,t ot he best of our knowledge,a general method, which uses organoborons for the regioselec-tive functionalization of unprotectedc arbohydrates has not been reported. [14][15][16] This is because the organoboronc atalyst binds to both cis-1,2-diol and 1,3-diolm oieties (Scheme 1e). [12,14] Herein, we describe the chiral benzazaborole-catalyzed regioselective sulfonylation of unprotected carbohydrates.…”
mentioning
confidence: 99%
“…[21] The high catalytic activity of 1f would be derived by the electrond onation from the nitrogen atom ontot he boron center.I ntroduction of am ethoxy substituent on the quinoline ring did not improvet he chemical yield ( [10][11][12][13][14]. Among the tested solvents, acetonitrile gave the best result( Ta ble 1, entries [15][16][17][18][19]. In the absence of organoboron catalyst, the reactiond id not proceed at all (Table 1, entry 20).…”
mentioning
confidence: 99%